2013
DOI: 10.5539/ijel.v3n2p98
|View full text |Cite
|
Sign up to set email alerts
|

Compound Prepositions Used by Iraqi EFL University Students

Abstract: There is no logical reason why one compound preposition is right in a certain context, whereas another one is wrong. To use compound prepositions correctly is difficult because most of them have several functions. In addition, different prepositions have sometimes similar uses. Such prepositions cause difficulty to Iraqi EFL university students because syllabus designers and teachers do not concentrate on such sort of prepositions. This study aims at identifying and analyzing the errors Iraqi EFL university st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…The findings were consistent with previous findings (Mahmoodzadeh, 2012;Humeid, 2013;Khampang, 1974;Ruangjaroon, 2015).…”
Section: %supporting
confidence: 93%
See 2 more Smart Citations
“…The findings were consistent with previous findings (Mahmoodzadeh, 2012;Humeid, 2013;Khampang, 1974;Ruangjaroon, 2015).…”
Section: %supporting
confidence: 93%
“…The results showed that most of the subjects did not recognize or use the prepositions because they did not understand the meaning or usage of such prepositions. The students' errors were assumed to be greatly affected by interlingual transfer, intralingual transfer, context of learning, and communication strategies (Humeid, 2013). Schneider & Zipp (2013) examined new verbpreposition combinations in four corpora of English varieties: International Corpus of English (ICE) Fiji, ICE India, ICE Great Britain, and ICE New Zealand.…”
Section: Previous Studies On L2a Of English Prepositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To exemplify, participants used 128 refusal strategies with lower interlocutors and identically, they employed 168 strategies with equal interlocutors whereas they used 218 strategies with higher interlocutors. Such a result was also obtained in the study of Humeid and Altai (2013).…”
Section: Discussionsupporting
confidence: 75%
“…In line with Beebe et al’s (1990) taxonomy, refusals in this setting fell into 3 broad categories: direct, indirect, and adjuncts to refusals. Similar to previous investigations among learners of English as a foreign language, nursing students in this setting leaned toward using direct refusal strategies, especially when refusing a request (Abu Humeid & Altai, 2013; Al-Mahrooqi & Al-Aghbari, 2016; Çiftçi, 2016). Semantic formulas, including the use of “lack of empathy” and “reprimand” to address a higher-status person, emerged as problematic refusals that, if used in real settings, may lead to communication breakdown, as they impose a threat to the interlocutor.…”
Section: Discussionsupporting
confidence: 53%